The taxonomic stability imperative - Heterick, Brian; Majer, Jonathan (Royal Zoological Society of New South Wales, 2018)
Taxonomic stability is essential if the requirements of a host of stakeholders - health professionals, farmers, environmental consultants and public servants, to name just a few occupations – who need advice on particular organisms are to be satisfied. In many cases this involves the production of species lists. Reliably identified lists of species of one or more groups of taxa are desirable if not mandatory for decision making by stakeholders in environmentally-based long-term research. Both straightforward factors (i.e., quality of the taxonomy that is associated with the species list) and more complex factors behind the compilation (the philosophical undergirding that determines how the species are differentiated in the first place) can often make its interpretation a problematic undertaking, particularly when taxonomic changes occur during the course of long-term studies. Concepts behind the naming of species can deal with patterns or with underlying processes. Whichever way it is undertaken, traditional taxonomy is often slow. This paper evaluates recent attempts to devise cheap, cost effective methods (i.e., barcoding, metagenomics) that will make the taxonomic process more uniform, less labor intensive and hopefully more stable over time.